Dark-Skinned Woman's Image Represented in Avon's Catalogue 2022 “WHAT'S NEW” Cosmetic Advertisements: A Semiotic Study - Diharjo, Marciella Liauwren; Fadilah, Eka; Linuwih, Endar Rachmawaty (Journal of English Language and Pedagogy (JELPA), 2023)
In this case, the researcher wants to analyse three advertising posters for the Avon Catalog 2022 product “WHAT'S NEW” out of a total of singers representing dark-skinned women using semiotics. The dark-skinned women who became the object symbolized that the advertised product was suitable for all skin types. This study employs a qualitative approach with descriptive analysis. Therefore, this study aims to identify the signs (icon, index, symbol) and find out the meaning of messages contained in advertising posters through Peirce's theory. The results of this study indicate that there are 13 signs on 3 Avon advertising posters (Eye Love It, Luxury In The Shade of You, Winter-proof Your Skin). Besides that, the researcher also found the meaning of each symbol by using dark-skinned women, which shows that they can also positively impact the beauty world. It could be concluded that each advertisement had a different sign, and this distinct difference had given different interpretations. From the semiotics analysis of ads, the advertiser's complex idea can be quickly delivered by the cons quickly